Multi‐section branch‐line couplers for crossover application. Issue 7 (July 2017) - Yeo, S. P.; Deng, N.
Abstract: Other researchers have already designed 1‐, 2‐, 3‐, and 4‐section versions of the branch‐line coupler for crossover application. The focus of this article is on the 5‐, 6‐, and 7‐section versions. Laboratory tests show that the resulting crossovers have bandwidths of 49%, 54%, and 59% respectively.